1980
DOI: 10.1111/j.1751-1097.1980.tb03991.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates in the Room Temperature Flash Photolysis and Low Temperature Photolysis of Purine Solutions

Abstract: The Rash photolysis of purine in acetonitrile and in water at dimerent pH was studied. The transients produced on Rash excitation of degassed aqueous solutions have been identified as the triplet excited state, the hydrated electron, a purine radical cation and radical anion on the basis of quenching experiments and comparison to transients observed in low temperature photolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Assuming equal concentrations of 7MAde and crocetin triplets, a minimum 7MAde triplet concentration of 8 X lo-' M was estimated, 8 times higher than the triplet concentration observed in AdeH-irradiated solutions and a tenth of the aqueous electron concentration. A triplet-triplet absorption maximum at 405 nm with a lifetime of 55 ps has been reported for 2-aminopurine (Szabo et al, 1975) and an absorption band in the wavelength region of 340-470 nm was assigned to the purine free-base triplet state (Arce et al, 1980). If the 7MAde triplet state is an intermediate state in its photoionization mechanism, the absence of the 310-nm maximum in an 02-saturated solution could imply that this absorption is due to a transient species having a triplet precursor such as a 7MAde radical cation.…”
Section: -Methyladenine and 9-methyladeninementioning
confidence: 90%
“…Assuming equal concentrations of 7MAde and crocetin triplets, a minimum 7MAde triplet concentration of 8 X lo-' M was estimated, 8 times higher than the triplet concentration observed in AdeH-irradiated solutions and a tenth of the aqueous electron concentration. A triplet-triplet absorption maximum at 405 nm with a lifetime of 55 ps has been reported for 2-aminopurine (Szabo et al, 1975) and an absorption band in the wavelength region of 340-470 nm was assigned to the purine free-base triplet state (Arce et al, 1980). If the 7MAde triplet state is an intermediate state in its photoionization mechanism, the absence of the 310-nm maximum in an 02-saturated solution could imply that this absorption is due to a transient species having a triplet precursor such as a 7MAde radical cation.…”
Section: -Methyladenine and 9-methyladeninementioning
confidence: 90%
“…It has been proposed that the triplet state absorbs the second photon, but it has been difficult to detect this state in transient spectroscopy experiments. A triplet-triplet absorption for various Ade (25,28) and Gua (29,35) derivatives has not been detected upon their direct excitation with microsecond or nanosecond flash photolysis. But triplet absorption signals have been observed in the 380-470 nm wavelength region in experiments where the triplets were produced by photosensitization (65)(66)(67).…”
Section: Mechanism Of Pi For the Dna And Rna Bases At 266 Nm Nanosecomentioning
confidence: 94%
“…Previous studies have suggested that monophotonic PI of DNA and RNA bases could occur at ca 250 nm low-intensity irradiations (15,16,18,(35)(36)(37)(38). But the potential existence of a monophotonic pathway using either 248 or 266 nm laser excitation has received much less attention despite its great relevance to DNA photobiology.…”
Section: Pi Of the Dna And Rna Bases And Derivatives Through A Combinmentioning
confidence: 99%
“…As is known, MnC1, (34,35), O2 (27,35) and Xe (27.36) have been described as effective quenchers of triplet states.…”
Section: -Chloropurine 6-merhoxypurine 6-aminopurine (Adenine)mentioning
confidence: 97%